Methodische Überlegungen zur floristischen Pflanzengeographie - Frankenberg, Peter (ERDKUNDE, 1977)
Previous theories in the field of Arealkunde will be treated shortly before presenting some basic thoughts on a system of floristic analysis with the aim of undertaking a quantitative plant-geographical areal differentiation: Using floristic elements as a basis, elemental floristic spectra will be presented in a rectangular grid (Gitternetz); the area concerned will be classified in floristic regions according to dominant floristic elements. In addition to these considerations some quantitative methods for grouping floristic elements and the creation of elemental floristic spectra are proposed. Beyond this an attempt is made to integrate life form spectra in a floristic analysis. Furthermore posing of cartographical questions concerning elemental floristic spectra will be dealt with in some examples.